Hydromedusa tectifera Cope 1870 – South American Snake-necked Turtle, Argentine Snake-necked Turtle, Tortuga Cuello de Vibora, Cágado Pescoço de Cobra - Alcalde, Leandro (2021)
The South American Snake-necked Turtle, Hydromedusa tectifera (Family Chelidae), is a medium-sized freshwater turtle, found in southern Brazil, Uruguay, southern Paraguay, and east and central Argentina. Maximum recorded straight carapace length (CL) is 30.6 cm in females and 28.4 cm in males, although most individuals are usually less than 25.0 cm. Its skull and carapace structure show characters quite distinct from those of the superficially similar chelid snake-necked turtles of Australia (genus Chelodina). Clutch size is 5–15 eggs and eggs are elongate, ranging from ca. 24–40 x 20–24 mm; hatchlings have a CL of ca. 35–37 mm. Preferred habitats for H. tectifera consist primarily of natural lentic and lotic waters, including anthropogenically altered or constructed habitats (e.g., creeks, dams, lakes, lagoons, streams, rivers, and coastal estuaries). The species is specialized for feeding upon a wide spectrum of food items, mainly aquatic arthropods. The international pet trade in this species is modest, and although it seems to be affected by industrial and agricultural pollution in several parts of the range (e.g., Rio de Janeiro State in Brazil, Buenos Aires Province in Argentina), it shows considerably greater tolerance for polluted conditions than does its congener H. maximiliani.